2010
DOI: 10.3400/avd.cr01017
|View full text |Cite
|
Sign up to set email alerts
|

Multivisceral Fibromuscular Dysplasia: An Unusual Case of Renal and Superior Mesenteric Involvement

Abstract: Fibromuscular dysplasia (FMD), a disease process which leads to arterial stenosis and aneurysm formation, has been reported to occur in almost every arterial bed in the body. However, multivisceral FMD is rare, and we report a 43-year-old woman with hypertension who had incidental finding of FMD of both renal arteries and the superior mesenteric artery (SMA). The left renal aneurysms and right renal stenosis were successfully treated by aneurysm resection and aortorenal bypass and percutaneous transluminal ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Such pathologic changes are demonstrated by a "string-of-beads" appearance via angiography. [4][5][6] The "string-of-beads" appearance, which angiographically characterized medial FMD, occurs in about 70 % of cases. Specific features of adventitial or intimal FMD cannot be shown using angiography.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Such pathologic changes are demonstrated by a "string-of-beads" appearance via angiography. [4][5][6] The "string-of-beads" appearance, which angiographically characterized medial FMD, occurs in about 70 % of cases. Specific features of adventitial or intimal FMD cannot be shown using angiography.…”
Section: )mentioning
confidence: 99%
“…The medial fibroplasia is a major type of FMD, and 60%-70% of this type show "string-of-beads" appearance via angiography. [4][5][6][7] IVUS was useful in differentiation of FMD from atherosclerosis in such a focal stenosis type via angiography. Furthermore, IVUS images were useful in not only the evaluation of both the lesion diameter and lesion form, but also decision making of both balloon size and end point of strategy.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the pathology is progressive, we also considered administration of steroids for early treatment. However, due caution is required for the administration of steroids in cases where differentiation between inflammatory and noninflammatory arteriopathy is difficult because it can increase vascular fragility [3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, the aortorenal bypass is done using a saphenous vein or ePTFE graft to shorten renal warm ischemic time. 8) This patch angioplasty was done in another group. 9,10) Pfeiffer et al 9) reported no recurrence of aneurysms to be observed after tailoring in their series, and this may be because the aneurismal parts of the vessel wall were resected, leaving almost normal arterial wall next to the orifices of the branches.…”
Section: Discussionmentioning
confidence: 99%